Energy Analysis of the Refrigeration System and Its Impact on Process Parameter in Shortening Oil Production - Hartanto Hartanto; Dyah Retno Sawitri; Sholeh Mamun (Institut Teknologi Adhi Tama Surabaya, 2025)
The food industry continuously evolves to meet the increasing demand for high-quality products such as shortening oil. This study analyzes the performance of refrigeration systems in shortening oil production, focusing on the effects of suction pressure on energy efficiency and product quality. Experimental results demonstrate that increasing the suction pressure from 1,2 bar to 1,6 bar leads to a reduction in cooling capacity (Qe) from 110,08 kJ/kg to 91,36 kJ/kg, heat rejection capacity (Qc) from 137,34 kJ/kg to 122,85 kJ/kg, and the Coefficient of Performance (COP) from 4,04 to 2,90. Despite these declines in system efficiency, the penetration value (Pen.V) of the final product increased from 272 mm/s to 314,4 mm/s, indicating an improvement in the texture of the shortening oil. These findings underscore the critical role of optimizing suction pressure and operational parameters to balance energy efficiency and product quality. The study highlights the importance of maintaining precise control over refrigeration system variables to enhance production sustainability and meet industry standards.